Industry perception on the benefits of construction waste management strategies in the Philippines - Orozco, Christian R. (Philippine Engineering Journal)
The surge of construction projects in the Philippines has influenced construction industry attitudes towards construction waste management and environmental protection. As construction waste management is becoming an important factor in modern construction management, the Philippines construction industry has began to do its part in promoting and implementing means of managing wastes produced from construction activities. This paper discusses the result of conducted survey among Philippine construction industry stakeholders to minimize wastes, and the importance of environment as a construction factor. By identifying their perception, areas that require special attention can be identified leading to the development of better waste management plan. Results indicated that the majority of the stakeholders recognize that construction waste management has its benefits, which includes cost savings, increase in profit, reduced dumpsite disposal, improved company reputation and acquisition of new projects.